ANALISIS STRATEGI PENGAJARAN GURU PAI DALAM MENINGKATKAN KESADARAN SOSIAL SISWA DI MAN PANGKEP - Husain Abdullah; Heriady Heriady (IAI DDI Mangkoso, 2023)
This research aims to determine the strategies and success factors of PAI teachers in increasing MAN Pangkep students' awareness of social problems. This type of research is qualitative research with an approach that is appropriate to scientific disciplines, namely educational and psychological approaches. The data sources for this research are Islamic religious education subject teachers, madrasa heads, deputy madrasa heads, administrative staff, and several students. The data collection methods used were observation, interviews, and documentation. Data processing and data analysis techniques go through four stages, namely data collection, data reduction, data presentation, and conclusion. The results of this research show that: (1) The PAI teacher's strategy in increasing the social awareness of MAN Pangkep students is that the teacher provides educational, interactive, and exemplary interaction teaching methods, builds students' religious character, integrates religious values ??in learning to encourage students' social awareness, providing reflection activities and collaborating with parents and agencies. (2) The success factor in increasing the social awareness of MAN Pangkep students is involving students in social activities, increasing students' understanding of social values, and due to changes in students' attitudes and values. This research can have implications for improving PAI teaching methods and strengthening the role of schools in forming the character of students who have high social awareness, which in turn contributes positively to the wider community.